Nicotinamide adenine dinucleotide supplementation drives gut microbiota variation in Alzheimer’s mouse model - Chu, Xixia; Hou, Yujun; Meng, Qiong; Croteau, Deborah L.; Wei, Yong; De, Supriyo; Becker, Kevin G.; Bohr, Vilhelm A. (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is the most common neurodegenerative disease. Growing evidence suggests an important role for gut dysbiosis and gut microbiota-host interactions in aging and neurodegeneration. Our previous works have demonstrated that supplementation with the NAD+ precursor, nicotinamide riboside (NR), reduced the brain features of AD, including neuroinflammation, DNA damage, synaptic dysfunction and cognitive impairment. However, the impact of NR administration on the intestinal microbiota of AD remains unknown. In this study, we investigated the relationship between gut microbiota and NR treatment in APP/PS1 transgenic (AD) mice. Compared with wild type (WT) mice, the gut microbiota diversity in AD mice was lower and the microbiota composition and enterotype were significantly different. Moreover, there were gender differences in gut microbiome between female and male AD mice. After supplementation with NR for eight weeks, the decreased diversity and perturbated microbial compositions were normalized in AD mice. This included the species Oscillospira, Butyricicoccus, Desulfovibrio, Bifidobacterium, Olsenella, Adlercreutzia, Bacteroides, Akkermansia, and Lactobacillus. Our results indicate an interplay between NR and host-microbiota in APP/PS1 mice, suggesting that the effect of NR on gut dysbiosis may be an important component in its therapeutic functions in AD.